Primetime television shows and its relationship to the academic performance of the UPV-CM students - David, Albert Roy D.; Jangit, John Paul M.; Jumawan, Jay Ann E.; Magsisi, Leo S.; Mallada, Sylvie Ann F.; Ong, Jacquiline V.
It is already known that UPV-CM students are among the creme a la creme individuals of the Philippine National University. These kind of students balance their lives by doing exceptionally well in scholastic activity, as well as enjoying most, if not all, the pleasures of life. Outside the classroom, UPV-CM students engage in sports, music, journalism, social works, part-time jobs, and even in simple leisure activities, most especially watching primetime television shows contribute to their excellent academic performance? This study was conducted in order to answer that question. Two hundred and sixty students were given questionnaires that inquired on several matters that could affect their academic performance in relation to primetime television shows, namely, the type of primetime shows that they watch, the airing time of primetime shows that they watch, and the time spent in watching primetime shows. After the analysis of the data gathered from the respondents, and separately using regression analysis for each independent variable, ita was found out that the type of show, frequency in watching primetime television shows, and time allotted for studying have significant relationship with the academic performance of UPV-CM students. But it should be noted that the significance of these variables to the academic performance of UPV-CM students. But it should be noted that the significance of thes variables to the academic performance of UPV-CM students is only 11.4%, which means that there remains 98.6% of variables that still has to be considered. Thus, it is recommended that these remaining factors (e.g. other TV networks, recreational activities, extracurricular activities) be regarded by the students who plan to conduct a similar study in the future.